Remembering the AIDS Quilt - Morris, Charles E., 1969- (Rhetoric and public affairs series., 2011)
A collaborative creation unlike any other, the Names Project Foundation's AIDS Memorial Quilt has played an invaluable role in shattering the silence and stigma that surrounded the epidemic in the first years of its existence. Designed by Cleve Jones, the AIDS Quilt is the largest ongoing community arts project in the world. Since its conception in 1987, the Quilt has transformed the cultural and political responses to AIDS in the U.S. Representative of both marginalized and mainstream peoples, the Quilt contains crucial material and symbolic implications for mourning the dead, and the.